Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Guru di SMK TI Bali Global Jimbaran - Jayanti, Ni Wayan Sri; Devi, Ni Kadek Tasya Novita (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study is motivated by the importance of teacher performance as a determinant of education quality in SMK, particularly at SMK TI Bali Global Jimbaran, which is oriented toward the needs of technology-based industries. The principal’s leadership style and organizational culture are regarded as crucial factors influencing teacher performance. The purpose of this study is to analyze the effect of leadership style and organizational culture on teacher performance, both partially and simultaneously, as well as to identify the most dominant influencing variable. This research employs a quantitative approach with a population of 30 teachers as respondents. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability testing, multiple linear regression, t-test, F-test, and the coefficient of determination. The findings reveal that leadership style has a positive and significant effect on teacher performance, whereas organizational culture does not have a significant effect. However, simultaneously, both variables significantly affect teacher performance, with leadership style emerging as the dominant variable. The implications of this study highlight the importance of strengthening transformational leadership among principals to foster teacher motivation, performance, and professionalism, as well as the need for a supportive organizational culture to create a conducive work environment that enhances the quality of education.